THE THEORETICAL FOUNDATIONS OF PROVERB RESEARCH IN UZBEK LINGUISTICS - Gulnoza Ibodullayeva (Western European Studies, 2025)
This article explores the theoretical foundations of proverb research within Uzbek linguistics. It provides an overview of major linguistic approaches to the study of proverbs and highlights the role of Uzbek scholars in the development of paremiology. The paper discusses how proverbs function as culturally and semantically rich linguistic units and examines the methods used to classify, interpret, and compare them in Uzbek and related Turkic languages. Furthermore, the article analyzes the influence of global linguistic paradigms on Uzbek paremiological research and emphasizes the growing importance of comparative and interdisciplinary studies in understanding the nature of proverbs. Special attention is paid to the lexicographic, semantic, and pragmatic aspects of proverbs, as well as their role in the linguistic worldview and national identity
Keywords: Uzbek linguistics; paremiology; proverbs